2006
DOI: 10.1080/10408440600851377
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide: Review of Toxicity Data and Dose-Response Analyses for Cancer and Noncancer Effects

Abstract: Acrylamide (ACR) is used in the manufacture of polyacrylamides and has recently been shown to form when foods, typically containing certain nutrients, are cooked at normal cooking temperatures (e.g., frying, grilling or baking). The toxicity of ACR has been extensively investigated. The major findings of these studies indicate that ACR is neurotoxic in animals and humans, and it has been shown to be a reproductive toxicant in animal models and a rodent carcinogen. Several reviews of ACR toxicity have been cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
186
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(196 citation statements)
references
References 390 publications
2
186
0
2
Order By: Relevance
“…Acrylamide in food occurs at 120 °C or higher temperatures as a result of Maillard reaction between monosaccharides such as fructose or glucose and amino acids such as asparagine (7). The studies show that acrylamide is absorbed in a very rapid and effective manner by means of gastrointestinal system (8,9).…”
Section: Introductionmentioning
confidence: 93%
“…Acrylamide in food occurs at 120 °C or higher temperatures as a result of Maillard reaction between monosaccharides such as fructose or glucose and amino acids such as asparagine (7). The studies show that acrylamide is absorbed in a very rapid and effective manner by means of gastrointestinal system (8,9).…”
Section: Introductionmentioning
confidence: 93%
“…Most populations consume cooking-related meat mutagens at very low concentrations with skewed distributions such that few have high intake at which genotoxic and carcinogenic effects may occur and subsequent risk is observed. Biological thresholds are often observed with food-related genotoxic carcinogens (46), such that no adverse effect is observed unless an upper limit of exposure is exceeded (47 NOTE: Cohort that completed the meat-cooking module: n = 459 cases, n = 317,371 cohort subjects; 291 male cases, 183,650 male cohort subjects; 168 female cases; 133,721 female cohort subjects. *P trend calculated using median values for each quantile.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, since any level of exposure to a genotoxic substance could possibly cause DNA damage and lead to cancer, no tolerable daily Acrylic Polymers in Healthcare 160 intake (TDI) of ACR is set by European scientists [44], not to mention Africa. Nonetheless, Shipp et al [13] reported that ACR administered to drinking water of rodents at doses of ≥5 mg/kg bw/day resulted in significant decreases in the number of live pups. At higher doses, signs of copulatory behaviour as well as effects on sperm motility and morphology were observed by these authors.…”
Section: Toxicity Of Acrylamidementioning
confidence: 99%
“…Its application as a grouting agent is also extended to the construction of dam foundations, sewers and tunnels and cosmetics and in electrophoresis gels [13]. It has also been used in pesticide production, cement formulations, ore processing, sugar manufacturing, food packaging, plastic and paper production and for the prevention of soil erosion [2].…”
Section: Introductionmentioning
confidence: 99%